Sorting around the Discontinuity Threshold: The Case of a Neighbourhood Investment Programme - Sander Gerritsen; Dinand Webbink; Bas ter Weel (Institute for the Study of Labor (IZA), 2016)
This paper investigates the empirical validity of the setup of a large-scale government neighbourhood investment programme in the Netherlands. Selection of neighbourhoods into the programme was determined by their score on a predetermined index. At first sight this is a textbook example for the application of a regression discontinuity (RD) design to estimate the causal effect of the programme on neighbourhood outcomes. However, at the discontinuity threshold we find a large gap in the share of non-Western immigrants. In addition, the pattern of non-compliance with the assignment rule is consistent with investing in neighbourhoods with a high share of non-Western immigrants. Finally, the way of selecting neighbourhoods into the programme could be a likely explanation for the imbalance at the discontinuity threshold. This case illustrates that RD designs can become invalid even when treatment and control groups have no influence on the assignment.
Keywords: C90; D70; R58; 330; regression discontinuity designs; government decision-making processes; neighbourhood investment programmes